The Relationship Between Interest in Playing Football and Active Participation in Physical Education Learning at Sambung Jawa Complex Public Elementary School - Muhammad Qasash Hasyim; Sudirman (Journal Physical Health Recreation (JPHR), 2025)
This study aims to determine the relationship between interest in playing soccer and active participation of students in physical education classes at SD Negeri Kompleks Sambung Jawa. The study used a quantitative correlational approach with purposive sampling. The sample consisted of 60 fifth and sixth grade students. Data were collected through a soccer interest questionnaire and an active participation observation sheet, analyzed using Pearson Product Moment correlation test. The results showed that 70% of students had a high interest in soccer and 65% demonstrated active participation in PJOK. The correlation analysis yielded a value of r = 0.64 with p = 0.000, indicating a positive and significant relationship between the two variables. Interest in playing soccer was proven to positively contribute to students' active participation levels in PJOK. The implications of these results highlight the importance of an interest-based learning approach in physical education at the elementary school level.